The Effect of Using the Guided Imagination Strategy on Enhancing Creative Thinking Skills Among Female Students in the Department of Arabic at The College of Education for Women in Tikrit University - Shehab, Thabet Jaddoa (Journal of Tikrit University for Humanities, 2025)
This study aimed to identify the effect of using guided imagery strategy on enhancing creative thinking skills among female students of the Arabic Language Department at the College of Education for Women at Tikrit University. In order to answer the study questions, the researcher adopted the descriptive approach. The study population consisted of female students of the Department of Arabic in the College of Education for Women in Tikrit University, numbering 279. The study sample included 80 female students from the Department of Arabic in the College of Education for Women in Tikrit University. The study concluded with a set of recommendations. One of these recommendations is the necessity of using the guided imagery strategy in teaching Arabic, as it is a modern teaching strategy, and developing training programs and seminars to train faculty members before and during service on the importance of following the guided imagery strategy and not relying on memorization and indoctrination.